Faktor Penyebab Perilaku Penjualan dan Pembelian Antibiotik Tanpa Resep Dokter - Novita Dewi; Debby Juliadi (Jurnal Farmasi & Sains Indonesia, 2021)
Pharmacies are the main source of getting antibiotics. Access to antibiotics without a prescription at pharmacies is common in many countries, including Indonesia. The sale of antibiotics without a prescription in pharmacies has become a global problem, especially in developing countries. However, the dominant factor that causes the behavior of selling antibiotics without a prescription in Indonesian pharmacies is not known with certainty. The purpose of this article is to find out the dominant factors that influence the behavior of selling and using antibiotics without a doctor's prescription in pharmacies. The method used is by conducting library searches on search sites such as Google Schler with the keywords "antibiotics without a prescription, patient behavior, pharmacists, pharmacies". Where the results are factors that influence sales behavior and use of antibiotics without a doctor's prescription, namely the ease of access to antibiotics and cost savings factors, patient attitudes and recommendations from friends/relatives.